Penerapan Hazard Analysis Critical Control Point (HACCP) pada UKM Produksi Kerupuk Udang - Kosasih, Wilson; Florencia, Gabby; Andres; Salomon , Lithrone Laricha (Jurnal Rekayasa Sistem Industri, 2025)
Food quality is very important so that food processing must be done properly to ensure food safety, namely by implementing the HACCP system. HACCP is often considered a complex system so that not many companies use it. This study aims to prevent hazards that may arise using the HACCP system and evaluate the quality control of shrimp crackers to reduce defective products.. This study uses a case study approach to a small and medium-sized company that produces raw shrimp crackers. Data were collected through literature reviews, interviews, and observations. The techniques used are quality control, Good Manufacturing Practices – GMP, Sanitation Standard Operating Procedure – SSOP, and Hazard Analysis Critical Control Point – HACCP. The results of the quality control analysis show that products that are included in the Not Good category have the characteristics of being incomplete, untidy, clean, not uniform, and of uneven thickness. The GMP & SSOP analysis results show that this company is at level IV, and is included in the "Unfit" category and HACCP analysis show that there are three processes included in the Critical Control Point (CCP), namely storage of raw and packaging materials, drying, and storage of finished materials. Suggestions for improvement are this company needs to pay more attention to quality control, improves the implementation of GMP and SSOP so that they can reach Level I in GMP and the "Meet" category in SSOP, and only then can implement the HACCP plan.